Three-dimensional Ising-like system in an external field: Microscopic calculation of the free energy in the higher non-Gaussian approximation - Pylyuk, I. V. (Phase transitions, 2007)
An analytic method for deriving the free energy of a three-dimensional Ising-like system near the critical point in a homogeneous external field is developed in the the ρ 6 model approximation. The mathematical description proposed for temperatures T>T c (T c is the phase-transition temperature in the absence of an external field) is valid for fields near , where the scaling variable is of the order of unity and power series in this variable are not effective. At the limiting field , the temperature and field effects on the system in the vicinity of the critical point are equivalent. The total free energy is obtained as a function of temperature, field and microscopic parameters of the system without using series expansions in the scaling variable. In addition to leading terms, the expression for the free energy includes the terms determining the temperature and field confluent corrections.